Knowledge, opinions and experiences of nurses and nursing students in Portugal regarding the use of medical Cannabis - Catarina Paiva; Teresa Santos; Aliete Cunha-Oliveira; Inês Rosendo; João-Rui Pita (BMC Nursing)
Abstract Background The opening up of the laws to medicinal cannabis in recent years is a key factor in the growth of this therapy, but there is little information about what nurses know and think about it. The present paper seeks to analyze the knowledge, opinions, and experiences of nurses and nursing students in Portugal regarding the use of cannabis and to understand gender differences. Methods A self-completion questionnaire was drawn up and published online. It received face and content validity and was approved by the Ethics Committee. The instrument includes socio-demographic data, questions about knowledge, opinions, experiences, and training in cannabis. The data was collected and processed by applying descriptive and inferential statistics using the chi-square test and Fisher’s exact test on the SPSS platform. Results The majority of the 610 participants were women. The therapeutic benefits of medical cannabis were appreciated by 79,6% of nurses and 84,3% of students. When asked about the functions of the endocannabinoid system, 71,7% of nurses and 79,5% of students had never heard of it. There is a statistically significant gender difference concerning personal experience of cannabis use to treat symptoms or illnesses. Conclusions As the levels of knowledge were low and a minority had education on medical cannabis, there is a need for further education of nurses and for this emerging area to be included in the curricula.